MIGRASI INTERNASIONAL PERILAKU PEKERJA MIGRAN DI MALAYSIA DAN PEREMPUAN DITINGGAL MIGRASI DI LOMBOK TIMUR - Lalu Tajuddin, R. Rijanta, Hadi Sabari Yunus, dan Sri Rum Giyarsih (Universitas Gadjah Mada, 2015)
The goal of the research is to examine the behavior of migrant workers and PADMI. The research islocated in Eastern Malaysia and East Lombok Regency by using case study method to explore theobjects deeply, detailed and complete. Data were collected through observation and in-depth interviewwith the migrant workers and PADMI. The research showed that Ringgit or Malaysian currencycontribute significant influence to the migrant workers’ behavior, which showed by the change of theirfashion style, pattern of consumption, increasing entertainment needs and also the augmentation ofconsumptive life style. The consumptive life style is a new reality and relatively common, while to fulfillsexual needs the workers opted to marry the other female migrant workers because it was consideredmore save, more economical and also could prevent them from the contamination of sexual disease.At the other side, PADMI has not only principal role in fulfilling the family life needs but also mustattempt to maintain the completeness and harmony of the family/household. The inclination of havingseductive and sexual discomfiture from the other man is experienced often by PADMI, and sometimescould be ended in court. Without considering the economic impact, the high number of sued divorce inhometown of migrant workers gave evidence that migration activity ruin the family life of the migrantworkers.